Pelatihan Peningkatan Literasi Digital Marketing pada UMKM Persewaan Tenda Kecamatan Tembalang - Dhaifina Idznitia Apriyani Naimi; Rhealin Hening Karatri; Dina Lusianti (Universitas Muria Kudus, 2023)
The Covid-19 pandemic going on for an entire year in 2020 has impacted many aspects of life in Indonesia. This situation forces us as social creatures to find new ways to socialize, work, and perform various daily activities safely. The impact of social distancing concept makes industry players or SMEs in 2021 must be able to respond to what the community needs directly by changing the business model, including SMEs renting party equipment and tents. Marketing that has been done offline needs to be changed by using digital marketing media, which is currently very influential in the business world. Through Instagram, SME players can take advantage of various marketing features that can attract many prospective strategic consumers more efficiently and effectively to be implemented during this pandemic. The selection of Tembalang District as a target group in community service because Tembalang District is the 2nd district with the most significant number of SMEs in Semarang City.